2014
DOI: 10.1016/j.foreco.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timber harvesting on terrestrial survival of pond-breeding amphibians

Abstract: a b s t r a c tSuccessful forest management for multiple uses requires balancing extractive practices with maintaining biodiversity, among other important goals. Amphibians comprise an important and abundant part of the biodiversity of many forests. Previous studies have documented declines in the abundance and diversity of amphibians in harvested forests. However, only recently have studies begun to elucidate the mechanisms that underlie such declines. Here, we studied the effects of timber harvesting on surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…Moreover, these studies show that individuals move significantly greater distances in forest compared to open areas, presumably due to higher mortality in open areas Semlitsch 2002, Popescu andHunter 2011). For example, wetland-breeding salamanders have significantly lower survival rates in clearcuts than in unharvested controls (Todd et al 2014). For example, wetland-breeding salamanders have significantly lower survival rates in clearcuts than in unharvested controls (Todd et al 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, these studies show that individuals move significantly greater distances in forest compared to open areas, presumably due to higher mortality in open areas Semlitsch 2002, Popescu andHunter 2011). For example, wetland-breeding salamanders have significantly lower survival rates in clearcuts than in unharvested controls (Todd et al 2014). For example, wetland-breeding salamanders have significantly lower survival rates in clearcuts than in unharvested controls (Todd et al 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Salamanders may be particularly vulnerable to elevated temperatures, given that most salamanders tend to maintain lower body temperatures than frogs (Brattstrom 1963, Feder et al 1982) and snakes (Brattstrom 1965). Indeed, Todd et al (2009Todd et al ( , 2014 found that salamanders were more likely to avoid forest clearcuts than frogs and exhibited reduced survival in clearcuts. In addition to elevated temperatures, the absence or reduced abundance of many species were also likely caused by the lack of CWD, which is used or required for a range of important life functions, such as egg laying and shelter (LeGros et al 2014).…”
Section: Effects Of Structural Alterations Of Terrestrial Habitatmentioning
confidence: 99%
“…In enclosure experiments designed to test survival, Rothermel and Semlitsch (2006) and Todd et al (2014) found that only 17% of juvenile A. maculatum survived to the end of their first growing season. Because of the acute risk of desiccation, selecting a refuge may be the single most important decision made by a juvenile amphibian in its first night of movement through terrestrial habitat (Rothermel and Luhring 2005).…”
Section: Effects Of Habitat Manipulationsmentioning
confidence: 99%